Implementation of Visual and Performing Arts (VPA) in ELT Through Kampus Mengajar Program at Secondary School in Southwest Papua - Hasyim, Ruslan; Hasanudin, Hasanudin; Wael, Ahmad; Saputra, Dian; Hardianti, Rinda; Uluelang, Kris; Srianah Amir, Hasbiyah; Mohammad Sata, Mohammad Rafi'i (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This research discusses the implementation of Visual and Performing Arts (VPA) in the Campus Teaching Program at SMP Negeri 1 Kota Sorong, Southwest Papua. The research methodology employed is descriptive analysis, involving eighth-grade students as research subjects. Various work programs were implemented, such as Canva-based digital learning, "Spin the Wheel" games, collective film-watching activities, the Zero Waste program, and digital crossword puzzles. The research results indicate that the implementation of VPA has had a positive impact on students' learning experiences, enhancing technological skills, student interest, environmental awareness, and students' enthusiasm in answering questions. Additionally, visual and performing arts also contribute to the success of English language instruction. This research also highlights the importance of creativity in the language teaching process and the role of media, especially technology, in enhancing the effectiveness of teaching and learning. In conclusion, the implementation of VPA in the Campus Teaching Program has successfully enriched students' learning experiences through the obtained activity results.